Romanian´s attitude regarding information sources about healthy food products - Cînpeanu, Oona Cristina (2019)
Introduction: Over time, the Romanian people have undergone various lifestyle changes adapted to food availability, sources of information and social status. Aims: The main purpose in this study was to evaluate the most widely used sources of information as regards to a healthy diet and favorite food products, in order to establish the perception of individuals about their trust in sources of information and their efficiency. Materials and Methods: We performed a study based on the assessment of lifestyle and food behavior, which consisted in a validated questionnaire of 26 questions, applied online, to a group of 821 adults, in Romania, in 2018. Results: We explored the potential benefit to the Romanian population, segmented by age, gender, background, graduate level and current professional activity, in determining the main sources for nutritional information and the level of trust in these sources. According to this study, the most used sources of information by Romanians in the increasing order of frequency were: radio (14.6%), medical field (16.9%), school (21.8%), family and friends (29.5%), TV (30.8%), magazines, books, newspapers (34.6%), internet (47.5%), most interested being educated young women from urban areas. Conclusion: Nutritionists and food stakeholders should promote healthy diet through adequate sources of information, using eLearning methods, aimed to target groups.